Cultural and Creative tourism in Portugal - Carvalho, Rui (2016)
A new paradigm in the tourism industry is changing the meaning of culture and its use in promoting several touristic products/experiences and destinations. The questions we want to answer are the following: How can creative tourism be important in a destination and what are its implications in its organization? Methodology was based on the bibliographic review related to the object of study, data and content analysis, “snowball sampling” technique, surveys and participant observation technique. This paper analyzes how the event MED Festival in Loulé, Algarve has improved local economy, solved urban problems in the historical center (venue of the event) and helped to differentiate touristic supply in the mature touristic destination in the Algarve, Portugal.